2022
DOI: 10.1186/s12974-022-02528-5
|View full text |Cite
|
Sign up to set email alerts
|

Transient neuroinflammation following surgery contributes to long-lasting cognitive decline in elderly rats via dysfunction of synaptic NMDA receptor

Abstract: Background Perioperative neurocognitive disorders (PNDs) are considered the most common postoperative complication in geriatric patients. However, its pathogenesis is not fully understood. Surgery-triggered neuroinflammation is a major contributor to the development of PNDs. Neuroinflammation can influence N-methyl-D-aspartate receptor (NMDAR) expression or function which is closely associated with cognition. We, therefore, hypothesized that the persistent changes in NMDAR expression or functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 91 publications
0
4
0
Order By: Relevance
“…Recently, numerous studies have reported that young plasma reduces the spontaneous cognitive function of aged rats by improving hippocampal synaptic plasticity ( Gao et al, 2021 ; Chen et al, 2022 ; Xue et al, 2022 ). Given that the mechanism of cognitive function impairment during the aging process is similar to that following surgery and that the disruption of synaptic plasticity is also an important mechanism in the occurrence and development of postoperative cognitive impairment in older adults, we predicted that pre-infusion of young plasma would reduce the occurrence of POCD by improving hippocampal synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, numerous studies have reported that young plasma reduces the spontaneous cognitive function of aged rats by improving hippocampal synaptic plasticity ( Gao et al, 2021 ; Chen et al, 2022 ; Xue et al, 2022 ). Given that the mechanism of cognitive function impairment during the aging process is similar to that following surgery and that the disruption of synaptic plasticity is also an important mechanism in the occurrence and development of postoperative cognitive impairment in older adults, we predicted that pre-infusion of young plasma would reduce the occurrence of POCD by improving hippocampal synaptic plasticity.…”
Section: Discussionmentioning
confidence: 99%
“…Noted, that glutamatergic NMDAR plays a central role in PFC activity and its cognitive functions such as working memory, attention and reversal learning (20)(21)(22)(23). In addition, NMDAR is also associated with in ammation (53,54), and previous study demonstrate a remarkable increase in NMDA (NR2A and C) mRNA expression after viral-like brain in ammation (53). Here, we observed poor performance of mice in 5-CSRT after MW exposure with increased omissions and decreased correct responses accompanied by elevated expression of NMDAR (NR2A and NR2B).…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the past decades, surgery-related cognitive impairment has been linked to neuroinflammation. A major factor in the development of cognitive impairment has been proposed to be the release of proinflammatory cytokines [ 18 , 23 , 24 ]. It has been demonstrated that the neuroinflammatory response during POCD pathophysiology is affected by variations in the levels of proinflammatory cytokines in the cerebrospinal fluid of postoperative patients.…”
Section: Discussionmentioning
confidence: 99%